2022
DOI: 10.1038/s41598-022-23362-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ultrasound-guided fascia hydrorelease on the coracohumeral ligament in patients with global limitation of the shoulder range of motion: a pilot study

Abstract: We conducted a prospective single-arm interventional study of the treatment efficacy of ultrasound-guided fascia hydrorelease (US-FHR) on the coracohumeral ligament (CHL) of patients with global limitation of shoulder range of motion (ROM) without local inflammation. The primary outcome was the change in passive ROM (pROM) of external rotation (ER) after first US-FHR. Secondary outcomes included the change in pROM of other directions from baseline, the pain visual analogue scale (pVAS) at the timepoints after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Actually, all cases in our study were able to perform IR in the neutral position without problems. Kimura H et al reported that USguided fascia hydrorelease on the CHL in patients with shoulder contracture improved the ROM not only in ER but also in flexion, extension, abduction, and IR [24]. The anterior part of the CHL envelopes the subscapularis muscle, and the posterior part envelopes the supraspinatus/infraspinatus muscle, anchoring the muscles to the coracoid process.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, all cases in our study were able to perform IR in the neutral position without problems. Kimura H et al reported that USguided fascia hydrorelease on the CHL in patients with shoulder contracture improved the ROM not only in ER but also in flexion, extension, abduction, and IR [24]. The anterior part of the CHL envelopes the subscapularis muscle, and the posterior part envelopes the supraspinatus/infraspinatus muscle, anchoring the muscles to the coracoid process.…”
Section: Discussionmentioning
confidence: 99%
“…US-FHR or ultrasound-guided fascia hydrodissection (US-FHD) have recently gained popularity as therapeutic options for the management of fascial pain [18][19][20]. The term "hydrorelease" and "hydrodissection" refers to the separation and relaxation of fascial structures using the hydraulic force of injected solutions, typically D5W (5% dextrose in water).…”
Section: Ultrasound-guided Fascia Hydrorelease (Us-fhr)mentioning
confidence: 99%
“…The utilization of ultrasound guidance throughout the procedure allowed for precise targeting of the affected fascial structures and real-time monitoring of the injectate dispersal. This technique has also been reported to be effective in the management of pain syndromes in the shoulder, low back, and postarthroscopic knee scarring [18,19].…”
Section: Video 2: Ultrasound-guided Hydrorelease/hydrodissection Of S...mentioning
confidence: 99%
“…Finally, US-guided hydrorelease of the coracohumeral ligament is a promising new technique for the treatment of FS; however, more study is needed before this can be recommended for regular use (41).…”
Section: Injection-based Treatmentmentioning
confidence: 99%